Organizational and Technological Aspects of the Activities of the Convergent Editorial Office - M. N. Kim; E. M. Puck (Управленческое консультирование)
In the article, the authors consider various aspects of the functioning of convergent media editorial offices. For this purpose, organizational and technological innovations were studied. They have become actively introduced into the practice of editorial activity in recent decades. The merger of several media channels into large media holdings led to the fact that on the basis of such editorial conglomerations, specialized Internet departments and services first began to emerge, and then independent multimedia editorial offices. In the course of the study, employees of convergent media were interviewed, who told not only about the principles of organizing the production process for the release of multimedia products, but also about the features of introducing new forms of management of the editorial team, about various planning methods, and finally, about the functional tasks of new media employees.